Peningkatan Kemampuan Berbicara di Depan Kelas Melalui Model Pembelajaran Storytelling - Wahyuni, Wiwik Dwi; Suhartono, Edi; Al Atok, A. Rosyid (Universitas Negeri Malang, 2021)
One of the problems encountered during the learning process was the low ability to speak in front of the class. This study aimed to improve speaking skills using the storytelling learning model in Pancasila and civic education subjects. This study was a second-cycle class action research consisting of four phases: planning, implementation, observation, and reflection. Data analysis in this study was carried out through three stages, namely data reduction, data presentation, and conclusions. The analysis results found an increase in students' speaking ability at each meeting. It had proved that students' speaking ability in Pancasila and Citizenship Education subjects increased with the application of the storytelling learning model.